Institutions and public agricultural investments: A qualitative study of state and local government spending in Nigeria - Mogues, Tewodaj; Olofinbiyi, Tolulope (International Food Policy Research Institute, 2016)
This paper makes a contribution to this literature by drawing on the framework of actor-centered institutionalism (Scharpf 1997) to empirically examine how political and budget institutions affect the incentives of actors involved in the public agricultural finance process, structures the interactions between them, and ultimately shapes expenditure allocations